Visitor Perceptions of the Educational Fish Pond Tourism Site in Sumber Rejeki Hamlet, Loh Sumber Village, Loa Kulu, East Kalimantan - Saputra, Aji Muhammad Dwin; Purnamasari, Elly; Abdusysyahid, Said; Syafril, Muhammad (Jurnal Ilmu Perikanan Tropis Nusantara (Nusantara Tropical Fisheries Science Journal), 2025)
The Educational Tourism Fish Pond of Sumber Rejeki Hamlet, Loh Sumber Village, serves as a potential medium for introducing fisheries-related activities, including aquaculture, aquatic resource management, and the sustainable application of fisheries technology to the community. The objective of this study was to examine visitors’ perceptions of the educational tourism fish pond in Sumber Rejeki Hamlet, Loh Sumber Village, Loa Kulu Subdistrict. The research was conducted from November to December 2024 using the accidental sampling method. The respondents consisted of 45 visitors to the tourism site. Data were analyzed using descriptive analysis with a Likert scale measurement. The results indicate that visitors’ perceptions of the educational tourism fish pond fall into the “very good” category (87.05), within the score range of 87–103. This evaluation was based on the following indicators: tourism object (13.38, very good), accessibility (7.87, good), facilities (39.64, very good), information and promotion (17.29, very good), and management services (8.87, good).